Lay Representations of Cancer Prevention and Early Detection: Associations With Prevention Behaviors - Helen W. Sullivan, PhD, MPH; Lila J. Finney Rutten, PhD, MPH; Bradford W. Hesse, PhD; Richard P. Moser, PhD; Alexander J. Rothman, PhD; Kevin D. McCaul, PhD (Centers for Disease Control and Prevention, 2010)
IntroductionThe Common Sense Model of illness representations posits that how people think about an illness affects how they try to prevent the illness. The purpose of this study was to determine whether prevention representations vary by cancer type (colon, lung, and skin cancer) and whether representations are associated with relevant behaviors.MethodsWe analyzed data from the Health Information National Trends Survey (HINTS 2005), a nationally representative survey of American adults (N = 5,586) conducted by telephone interview.ResultsRespondents reported that all 3 types of cancer can be prevented through healthy behaviors; however, fewer did so for colon cancer. More respondents reported screening as a prevention strategy for colon cancer than did so for lung or skin cancer. Representations were associated with colon cancer screening, smoking status, and sunscreen use.ConclusionRepresentations of cancer were associated with relevant health behaviors, providing a target for health messages and interventions.